2019
DOI: 10.1186/s12881-019-0910-z
|View full text |Cite
|
Sign up to set email alerts
|

Association of high sensitive C-reactive protein with coronary heart disease: a Mendelian randomization study

Abstract: ObjectivesWhether high sensitivity C-reactive protein (hs-CRP) has a causal effect on coronary heart disease (CHD) is unclear. This study investigated the causal effect of hs-CRP on CHD risk using Mendelian Randomization (MR) analysis.MethodsA total of 3802 subjects were recruited in the follow-up study. Linear regression model was used to evaluate the relationship between CRP polymorphisms and hs-CRP. Survival receiver operator characteristic curve method was used to explore the cut-off of hs-CRP on CHD incid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 20 publications
0
20
0
1
Order By: Relevance
“…Also, the differences in MPO-DNA complex levels between participants with and without prevalent CVD were small. However, in previous studies on CRP levels and the risk of CVD, small elevations in CRP levels within the normal reference range have been shown to be associated with CHD [ 38 40 ]. Thus, this indicates that low grade inflammation is a risk factor for CHD.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the differences in MPO-DNA complex levels between participants with and without prevalent CVD were small. However, in previous studies on CRP levels and the risk of CVD, small elevations in CRP levels within the normal reference range have been shown to be associated with CHD [ 38 40 ]. Thus, this indicates that low grade inflammation is a risk factor for CHD.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated circulating CRP is a risk factor for CVDs; [40] yet genetically predicted CRP was not associated with coronary heart disease [ 41 , 42 ]. Interestingly, our results showed that an elevated serum CRP concentration was associated with higher risks of any chronic disease and death, whereas genetic predisposition to higher CRP indicated lower death risk.…”
Section: Discussionmentioning
confidence: 99%
“…In ammation plays a key role in the formation, development and rupture of atherosclerotic plaques. In 2019, Zhuang conducted a randomized clinical trial, enrolling 3802 subjects followed up for 5.01 years, and it was found that hs-CRP was positively associated with the incidence of coronary heart disease in the general population [16]. In 2014, Daniel's study identi ed hs-CRP as an independent predictive factor of 30-day mortality in STEMI patients [21].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown the CRP to Alb ratio could be used as a sensitive marker of in ammatory process and predicting the prognosis of patients with AMI, critical illness, malignant tumor and severe septicemia [10][11][12][13]. Thus, the hs-CRP to Alb ratio (HCAR), calculated by dividing hs-CRP by Alb obtained from clinical blood biochemical examination, may be more valuable in indicating higher residual in ammation with malnutrition status than either alone [14][15][16].…”
Section: Introductionmentioning
confidence: 99%